Boron nanoparticle doped PVA polymer composite nanofibers: In vitro behaviors - Duygulu, Nilufer Evcimen; Balkas, Merve; Ciftci, Fatih; Kucak, Mine (ELSEVIER, 2025)
This study aims to address the limitations associated with boron sources that contain chemical impurities and to enhance the applicability of boron (B) nanoparticle-doped polyvinyl alcohol (PVA) composite nanofibers in biomedical applications using the electrospinning technique. Morphological analyses conducted through Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) confirmed uniform dispersion of B nanoparticles, with an average fiber diameter of 185.52 +/- 38.86 nm at a flow rate of 1 mL/h and an applied voltage of 9 kV. X-ray Diffraction (XRD) and TEM indicated the presence of rhombohedral crystalline B nanoparticles, while Fourier Transform Infrared Spectroscopy (FT-IR) revealed enhanced molecular interactions and the formation of new functional groups. Thermogravimetric Analysis (TGA) demonstrated an increase in the thermal stability of the PVA/B composite nanofibers. Water absorption and enzymatic degradation analyses showed that B nanoparticle doping accelerated lysozyme-induced degradation. Antibacterial activity tests exhibited distinct inhibition zones against E. coli (13.90 mm), S. aureus (6.34 mm), and C. albicans (21.30 mm). Biocompatibility evaluation using the MTT assay revealed a high cell viability rate of approximately 99.2 %, confirming the cytocompatibility of the composite fibers. Overall, the findings highlight the promising potential of PVA/B composite nanofibers as multifunctional materials for advanced wound care systems.
Keywords: Boron nanoparticle; Composite nanofiber; Antimicrobial; Cytotoxicity; Wound dressing; ELECTROSPUN; BONE; Chemistry